Visual motion detection thresholds can be reliably measured during walking and standing - DiBianca, Stephen; Jeka, John; Reimann, Hendrik (Frontiers in Human Neuroscience, 2023)
In upright standing and walking, the motion of the body relative to the environment is estimated from a combination of visual, vestibular and somatosensory cues. Associations between vestibular or somatosensory impairments and balance problems are well established, but less is known whether visual motion detection thresholds affect upright balance control. Typically, visual motion threshold values are measured while sitting, with the head fixated to eliminate self-motion. In this study we investigated whether visual motion detection thresholds: 1) can be reliably measured during standing and walking in the presence of natural self-motion; and 2) differ during standing and walking. Methods: Twenty-nine subjects stood on and walked on a self-paced, instrumented treadmill inside a virtual visual environment projected on a large dome. Participants performed a 2-alternative forced choice experiment in which they discriminated between a counterclockwise ("left") and clockwise ("right") rotation of a visual scene. A 6-down 1-up adaptive staircase algorithm was implemented to change the amplitude of the rotation. A psychometric fit to the participants' binary responses provided an estimate for the detection threshold Results: We found strong correlations between the repeated measurements in both the walking (R = 0.84, p < 0.001) and the standing condition (R = 0.73, p < 0.001) as well as good agreement between the repeated measures with Bland-Altman plots. Average thresholds during walking (mean = 1.04 degrees, SD = 0.43 degrees) were significantly higher than during standing (mean = 0.73 degrees, SD = 0.47 degrees). Conclusion: Visual motion detection thresholds can be reliably measured during both walking and standing, and thresholds are higher during walking.